Governance fragmentation and urban spatial expansion: Evidence from Europe and the United States - Silvia Beghelli; Gianni Guastella; Stefano Pareglio (Fondazione Eni Enrico Mattei (FEEM), 2019)
This study assesses the effects of urban governance structure on the spatial expansion of metropolitan areas. A more fragmented governance structure, represented by a high number of administrative units with decision power on land use per inhabitant, is expected to increase the competition between small towns in the suburbs of metropolitan areas to attract households and workers, which, in turn, induces more land uptake. We study empirically the relationship between administrative fragmentation and the spatial size of cities in a sample of 180 metropolitan areas in the contexts of the US and Europe in the period 2000-2012. Results shed light on the structural differences between the two broad regions and suggest that administrative fragmentation impacts positively on land uptake in both the United States and Europe, although to different extents.
Keywords: R12; R28; R52; 330; Land take; Governance fragmentation; City size; United States and Europe